OPTIMALISASI PERAN GURU DAN ORANG TUA DALAM MENINGKATKAN MUTU BELAJAR SISWA KELAS III UPTD SDN 58 KAPPANG - Sumiati; Mulyadi; Supriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The quality of student learning at the elementary school level, particularly in grade III which is a transitional phase from concrete to abstract learning, requires an optimal synergy between the role of teachers at school and parents at home. This study aims to describe and analyze the optimization of the roles of teachers and parents in improving the learning quality of grade III students at UPTD SDN 58 Kappang. A descriptive qualitative method was employed with data collection techniques including participant observation, in-depth interviews, and documentation. The research subjects included grade III teachers, the school principal, parents, and students. The results indicate that teacher role optimization is carried out through adaptive learning planning, varied teaching methods, and intensive communication with parents. Meanwhile, parent role optimization is manifested through learning assistance at home, creating a conducive learning environment, and active participation in school programs. Supporting factors include mutual commitment, open two-way communication, and parental understanding of child development. Inhibiting factors include time constraints, educational background limitations, and limited access to information. This study emphasizes the importance of building strategic partnerships between schools and families as a sustainable effort to improve the quality of basic education.